Dynamic Arterial Elastance Is Associated With the Vascular Waterfall in Patients Treated With Norepinephrine: An Observational Study - Bar, Stéphane; Nguyen, Maxime; Abou-Arab, Osama; Dupont, Hervé; Bouhemad, Belaid; Guinot, Pierre-Grégoire (Frontiers in Physiology, 2021)
Introduction: It has been suggested that dynamic arterial elastance (Eadyn) can predict decreases in arterial pressure in response to changing norepinephrine levels. The objective of this study was to determine whether Eadyn is correlated with determinants of the vascular waterfall (critical closing pressure (CCP) and systemic arterial resistance (SARi) in patients treated with norepinephrine. Material and methods: Patients treated with norepinephrine for vasoplegia following cardiac surgery were studied. Vascular and flow parameters were recorded immediately before the norepinephrine infusion and then again once hemodynamic parameters had been stable for 15 minutes. The primary outcomes were Eadyn and its associations with CCP and SARi. The secondary outcomes were the associations between Eadyn and vascular/flow parameters. Results: At baseline, all patients were hypotensive with Eadyn of 0.93 [0.47;1.27]. Norepinephrine increased the arterial blood pressure, cardiac index, CCP, total peripheral resistance, arterial elastance and ventricular elastance, and decreased Eadyn (0.40 [0.30;0.60]) and SARi. Eadyn was significantly associated with CA, CCP and TPRi (p< 0.05). Conclusions: In patients with vasoplegic syndrome, Eadyn was correlated with determinants of the vascular waterfall. Eadyn is an easy-to-read functional index of arterial load that can be used to assess the patient’s macro/microcirculatory status. Trial registration: Clinicaltrials.gov: NCT03478709. https://clinicaltrials.gov/ct2/show/NCT03478709?cond=dynamic+arterial+elastance&rank=2.